Mu opioid receptor activation in microglia enhances HIV-1 infection and HIV-infection-induced inflammatory responses - Skeete, Chelsey; Sgambettera, Gabriel; Gojanovich, Aldana D.; He, Xianbao; Bryant, Daniel; Yang, Mengwei; Banerjee, Shreya; Quiñones-Molina, Andrés A.; Akiyama, Hisashi; Mostoslavsky, Gustavo; Henderson, Andrew J.; Gummuluru, Suryaram (Frontiers in Immunology, 2025)
People living with HIV-1 (PWH) and chronically using opioids have elevated risks of developing HIV-associated neurological disorders (HAND) that are often correlated with persistent inflammation. Microglia, innate immune cells in the brain, are the principal HIV-1 reservoir in the central nervous system and regulate neuroinflammation. Our group previously showed that HIV-1 infection of induced pluripotent stem cell (iPSC)-derived microglia and viral intron-containing RNA (icRNA) expression triggers inflammatory responses. Microglia express μ opioid receptor, MOR, yet the immunomodulatory effects of opioids on HIV-1 infection in microglia are unclear. Here, we report that MOR activation impacts HIV-1 infection establishment and HIV-1-induced innate responses in microglia. Morphine pretreatment enhanced reverse transcription (RT), integration, viral transcription, and p24Gag secretion in HIV-1-infected iPSC-derived microglia, which was blocked by treatment with naloxone, a MOR antagonist. In contrast, morphine treatment did not impact HIV-1 infection in MOR-deficient monocyte-derived macrophages, although, induced exogenous expression of MOR in macrophages conferred morphine-mediated enhancement of HIV-1 infection. Interestingly, viral transcriptome analysis by digital-drop PCR revealed selective enhancement of HIV-1 icRNA expression in morphine-exposed iPSC-derived microglia, which correlated with enhanced HIV-1 icRNA-induced secretion of IP-10 in MOR+ cells. Further, PI3K inhibitor, wortmannin, blocked morphine-mediated enhancement of HIV-1 replication and HIV-1 icRNA-induced IP-10 secretion, suggesting that MOR signaling and HIV-1 icRNA expression synergistically activate the PI3K-Akt signaling pathway in microglia to exacerbate virus-induced inflammatory responses.